OPTIMALISASI APLIKASI CANVA DALAM UPAYA MENINGKATKAN UMKM - Febiansa, Kevin Zentha; Yuniarti, Tatik; Fakhran Al Ramadhan, Muhammad (Universitas Islam 45 Bekasi, 2023)
One of the skills that is needed for entrepreneurship is making a logo design to support entrepreneurial activities. Therefore, there is a need for training to improve the ability and creativity of individuals who want to become entrepreneurs. The purpose of this community service is to provide knowledge and skills to the community, especially the young people of Setiajaya Village, so that they are able to use the Canva editing application. The training materials that will be provided include presentation of material on how to use the Canva application in creating designs that are used for purposes such as making logos, promotional flyers and business product designs. The method used in this community service activity is providing training material through presentations and using the Canva editing application. The form of achievement from this community service activity is that training can be carried out on the use of the Canva editing application with a maximum number of participants of 20 participants who can take part in the training until the end of the event and it is hoped that participants will gain knowledge about using the Canva design application to improve the skills and creativity of young village children Setiajaya to start entrepreneurship.